Evidence on the volatility of Indian and Japanese stock markets. (9th August 2010) - Singh, Tarika; Mehta, Seema; Gupta, Deepali
The purpose of the present study is to find out the historical volatility of the CNX S&P Nifty and Nikkie225 stock exchanges of India and Japan, respectively. The researchers have also tried to find out the impact of treasury bond rates changes on insurance companies in Japan and banking companies in India. The study done is descriptive in nature where secondary sources were used to collect the data. Purposive sampling technique was used for sampling insurance and banking companies. The sample size was of 8 insurance companies from Nikkie225 and 15 banking companies from NSE CNX S&P Nifty stock exchanges (used in the formulation of index). The study resulted in checking of volatility of Indian Nifty and Japanese Nikkie225 stock exchanges where high-frequency volatility was found out in Nikkie225 exchange. Similarly, it was found that insurance companies of Japan are more volatile to treasury bond rate changes as compared to Indian banking companies.